BIOFILM IN CHRONIC DIABETIC FOOT ULCER-CASE REPORT - Telenta, Julija Mitrova; Gjatovska, Liljana Labacevska; Kostovski, Marko; Dimova, Maja; Karajovanov, Ivana Dohceva; Nikolovska, Suzana; Duma, Silvija; Breshkovska, Hristina; Panovski, Nikola (Journal of Morphological Sciences, 2023)
Diabetic foot ulcers(DFUs) as one of the most common complications in patients with diabetes mellitus are usually chronic wounds.The reason for its chronicity are infections and biofilm formation. We present a patient with diabetic foot neuropathic ulcer on the right foot. Microbiological swab showed isolates of  bacteria and fungi, Candida albicans,Enterococcus and Acinetobacter which were tested for biofilm formation with microtiter plate assay. Biofilm mass was evaluated spectrophotometrically by measuring the absorbence of crystal violet. Enterococcus was with high potential of biofilm formation. Wound surface was measured every week for a period of one month and it was reduced for 23.93%. Ulcer was treated with peroral antibiotic and antifungal medications and standard wound care was performed. Microorganisms isolated from wound swabs showed mixed bacterial and fungal components. Current sudies show that relation in between this biofilm is still unclear. All of this is a key role in treating chronic wounds, making it a challenge for everyone not only in the field of making  diagnosis , but also in the field of treatment.  Key words: diabetic foot ulcers(DFUs),bacteria, fungi, biofilm